UJI TOKSISITAS AKUT SENYAWA ASAM p-METOKSISINAMAT YANG DISINTESIS DARI ETIL p-METOKSISINAMAT - Sara Nurmala; Indah Zahara (JURNAL KIMIA MULAWARMAN, 2022)
Kencur (Kaempferia galanga L.) is a plant that grows in Indonesia and is often used as a traditional spice. The main content of Kencur is ethyl p-methoxycinamic has a mild level of toxicity. Hydrolysis results from Ethyl p-methoxycinamic namely p-methoxycinamic acid have been widely studied as having antibacterial activity against S. aureus with MIC of 125 ppm. P-methoxycinamic acid has anti-inflammatory activity, topical anti-inflammatory power of 8.7% p-methoxycinamic acid based on molar equality with 1% Na-diclofenac. Cinnamic acid compounds have greater potential as an inhibitor of cervical cancer cells compared to methyl cinnamon because they have more hydrogen bonds. Hydrolysis of ethyl p-methoxycinamic to p-methoxycinamic acid has been carried out, then identification tests have been carried out covering the melting distance obtained values ​​of 172–173ºC. The results of TLC analysis with the mobile phase of methanol: acetone (2: 1) p-methoxycinamic acid compound gave an Rf value of: 0.67. The results of infrared spectrum analysis of hydrolysis compounds provide information on the presence of specific functional groups, namely carbonyl groups of acids (C = O) which are shown by the absorption band at wave number 1690.49 cm-1. Hydrogen bonding in carboxylic acid dimers weakens the C = O bond, resulting in absorption at lower wave numbers. In this spectrum CO groups of acids are shown at absorption of 1029.92 cm-1, aromatic C = C groups are shown by uptake at wave numbers 1602.74 cm-1 and 1627.81 cm-1, while bands at wave number 828.37 cm-1 indicates the presence of para-substituted aromatic nuclei. Acute toxicity test of p-methoxycinamic acid compound which was carried out in a span of 24 hours showed that p-methoxycinamic acid had a moderate level of toxicity.